Edukasi Penerapan Gizi Seimbang Berbasis Pangan Lokal Bagi Ibu Hamil Dan Anak Balita Stunting Di Desa Waworoni Kabupaten Konawe Selatan : (Pemeriksaan Kehamilan, LILA dan Hb Ibu Hamil) - Trees, Trees; hikmandayani, hikmandayani; Bau, Abdul Syukur; Rundu, Rundu (Poltekkes Kemenkes Kendari, 2024)
Introduction Malnutrition is a chronic nutritional problem that is still a big challenge for Indonesia. Stunting is a condition where a child's body fails to grow at the age of five due to chronic malnutrition, which causes the child to be too short or not develop well for his age. There are still many pregnant women and people in rural areas who do not have sufficient knowledge about balanced nutrition and how to apply it in everyday life. Appropriate and sustainable balanced nutrition education is very important to increase the knowledge and skills of pregnant women and the community in implementing a healthy and nutritious diet to prevent and overcome stunting. Methods: Implementation methods for health education activities are lectures, face-to-face and question and answer discussions. Results: In general, Community Service activities are under the responsibility of the PPM (Research and Community Service) unit of the Kendari Ministry of Health Pol-Techkes. The stages of the Independent Health Education activity